Asynchronous patterns in soil bacterial diversity and functional potentials along an alpine altitudinal gradient - Li, Xianping; Li, Teng; Li, Huixin (Frontiers in Microbiology, 2024)
IntroductionAltitudinal changes in soil bacterial diversity, composition, biotic interactions, and function are prevalent. However, the overall patterns and associations among these dimensions remain unclear, particularly in vulnerable alpine mountain ecosystems.MethodsHere, we investigated soil bacterial communities along a high-altitude gradient to elucidate patterns and associations in taxonomic and phylogenetic diversity, co-occurrence networks, and functional potentials.ResultsWe observed increasing altitudinal trends in bacterial richness and phylogenetic diversity, along with significant differences in taxonomic and phylogenetic composition across altitudes. The connectivity component of the co-occurrence network properties showed a negative association with altitude. We also observed high redundancy in functional potentials, resulting in insignificant variation in functional diversity along the altitudinal gradient. However, the strength of functional diversity varied based on the interaction between network connectivity and phylogenetic diversity. Additionally, functional dissimilarity was more closely associated with phylogenetic rather than taxonomic dissimilarity or differences in network properties, highlighting the role of phylogenetic lineages in functional redundancy.DiscussionThis study characterizes the altitudinal distribution of soil bacteria and explores their covariations, enhancing our understanding of soil bacterial diversity and functional potentials along altitudinal gradients and providing valuable insights for predicting community changes and improving alpine ecosystem conservation.